Surface roughness models for end milling titanium alloy TI-6AL-4V under room temperature and preheated machining - Ginta, Turnad Lenggo; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul; Lajis, M. A. (2009)
This paper presents an approach in developing the first and second-order surface roughness models at 95% confidence level for end milling of titanium alloy Ti-6AI-4V using PCD inserts. The surface roughness models developed were for room temperature machining and preheated experiments. The cutting parameters for room temperature machining were the cutting speed, axial depth of cut, and feed while those for preheated machining experiments were cutting speed, feed, and preheating temperature. Vertical Machining Centre (VMC) was used for conducting the end milling operations using PCD inserts. High frequency induction heating was utilized for preheated experiments. Surface roughness values were measured using a surface roughness measuring instrument Mitutoyo Surftest Model SV-500. Design expert package software was used to establish the surface roughness models and the adequacy of the models were verified using analysis of variance at 95% of confidence interval.